PEMBELAJARAN ABAD 21: KEMBALI BERGURU PADA ‘FILOSOFI KENTONGAN’ SEBAGAI PELESTARIAN BUDAYA BANYUMAS - Aryani, Ine Kusuma; Abubakar, Wakhudin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The written article purposes were to discussed and interpreted the understanding of kentongan philosophy and the development of kentongan art and culture as an effort to preserve the local culture of Banyumas in the 21st century. This paper is accompanied by simple research using qualitative R&D. Data collected in from interviews that are described qualitatively. The results of the study are described in a qualitative description resulting in that Cipete Muhammadiyah elementary school students can understand the kentongan philosophy by liking kentongan art and culture; Cipete Muhammadiyah elementary school students are accustomed to playing kentongan cultural arts twice a week, so that they can win 1st champion in Banyumas Regency, as a physical proof of the love of local cultural arts and the main students as the next generation of the nation’s hope of love and pride in local indigenous culture, art Banyumasan Kentongan culture.